2021
DOI: 10.48550/arxiv.2104.14650
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Exact fluctuating hydrodynamics of active lattice gases -- Typical fluctuations

Tal Agranov,
Sunghan Ro,
Yariv Kafri
et al.

Abstract: We extend recent results on the exact hydrodynamics of a system of diffusive active particles displaying a motility-induced phase separation to account for typical fluctuations of the dynamical fields. By calculating correlation functions exactly in the homogeneous phase, we find that two macroscopic length scales develop in the system. The first is related to the persistence length of the particles and the other to the collective behavior of the particles. The latter diverges as the critical point is approach… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 69 publications
0
2
0
Order By: Relevance
“…Lattice models of interacting particle systems have also been used as paradigmatic models to study the non-trivial collective effects associated with dense particulate matter [55,56]. It has recently been shown that phase transitions resem-bling Motility Induced Phase Separation can be realized in lattice models with activity [15,57], however with microscopic rules different from our case. It would therefore be interesting to generalize our study to interacting active lattice walks to better understand the nature of the non-equilibrium phases that appear in collections of active particles.…”
Section: Discussionmentioning
confidence: 91%
“…Lattice models of interacting particle systems have also been used as paradigmatic models to study the non-trivial collective effects associated with dense particulate matter [55,56]. It has recently been shown that phase transitions resem-bling Motility Induced Phase Separation can be realized in lattice models with activity [15,57], however with microscopic rules different from our case. It would therefore be interesting to generalize our study to interacting active lattice walks to better understand the nature of the non-equilibrium phases that appear in collections of active particles.…”
Section: Discussionmentioning
confidence: 91%
“…They are known to generically exhibit a motility-induced phase separation [10][11][12][13][14][15][16][17][18][19][20][21][22][23] as a function of the density and the selfpropulsion strength of the active particles. While the behavior at the critical point has been under some debate, field theoretical arguments suggest that the terms which break time reversal symmetry are irrelevant at the critical point so that the system belongs to the Ising universality class [24][25][26][27][28]. Interestingly, these systems can be pumped by introducing a passive asymmetric object rather than a pump [29][30][31][32][33][34].…”
mentioning
confidence: 99%